Brief group psychoeducation for caregivers of individuals with bipolar disorder: A randomized controlled trial - Hubbard, A.; McEvoy, Peter; Smith, L.; Kane, Robert (Elsevier BV, 2016)
Background: Bipolar disorder is associated with significant impairment in personal and social functioning for the individual and their caregivers. Psychoeducation for caregivers is beneficial, but interventions have typically required a significant time commitment and have not assessed changes in self-efficacy. This study evaluated the effectiveness of a brief, two-session psychoeducational intervention for caregivers. It was hypothesized that the intervention would reduce caregiver burden and distress, and increase bipolar disorder knowledge and bipolar disorder self-efficacy. Methods: Participants (N=32) were randomized to immediate or waitlist control conditions. The intervention involved two, 150-minute group sessions spaced one-week apart. At pre-, post-, and one-month follow-up participants completed the Depression, Anxiety, Stress Scale (DASS-21), Burden Assessment Scale, Knowledge of Bipolar Disorder Scale, and a Bipolar Disorder Self-efficacy Scale. Results: Compared to the waitlist control group, the immediate treatment group demonstrated large and significant reductions in caregiver burden, and increases in bipolar disorder knowledge and bipolar disorder self-efficacy. These improvements maintained or increased to follow-up. No significant change was observed on the DASS-21. Limitations: Reliance on self-report and the sample comprised mostly of parents and partners, so it unclear if results generalize to other carer groups. Conclusions: Large and enduring improvements in carer burden, knowledge, and bipolar disorder self-efficacy can be achieved from a very brief, two-session intervention.